(untitled) (Research, Society and Development, 2021)
Cancer is one of the morbidities that most affect the population worldwide and is the cause of death for millions of people. In this sense, the present study aimed to detect associations between sleep disorders and other factors with Minor Psychic Disorders (PMD) in individuals with cancer treated at a specialized clinic in the interior of Bahia, Brazil. A cross-sectional study was carried out with 205 individuals diagnosed with some type of cancer, who were being treated at the High Complexity Unit in Oncology (UNACON), in which the sociodemographic profile, health condition and lifestyle of the participants was drawn. from a form through an interview. The outcome was determined according to the presence of Minor Psychic Disorder (MPD). Simple and relative frequencies were obtained and comparability between groups was performed using Pearson’s chi-square test or Fisher’s exact test, with a significance level of 5%. There was a predominance of females, prevalence of PMS of 63.44% among women (p=0.04), sedentary lifestyle, low education, income and presence of installed chronic disease. The study showed a positive and statistically significant association between insomnia and minor mental disorder, in addition to other factors found that are associated with the occurrence of these disorders. This survey was carried out among individuals undergoing antineoplastic treatment, which can be considered another factor for physical and psychological harm in these people’s lives.